A Novel Platform and Workflow for Underwater Photogrammetry Surveys - Mufti, Alaa Anas (Curtin University, 2024)
This thesis addressed challenges in underwater photogrammetry by developing a collapsible pyramid-shaped camera calibration frame; and a Raspberry Pi-based survey platform, equipped with GNSS, pressure sensor, and echosounder. The accuracy of the 3D models produced from underwater photogrammetry surveys increased by 36% when using a calibration frame; and by 55% when using the GNSS-PPK position data. Resulting in seafloor 3D models with an accuracy 30-50 cm in the horizontal, and 8-18 cm in the vertical.